Diplomacy and the birth of Islamic finance as an alternative financing source for the Global South. - Abubakar Usman, Abubakar; Muhd Huda, Mohd Ikbal; Adam Sa'ad, Auwal (Human Resource Management Academic Research Society, 2022)
Islamic finance (IF) is the latest form of international financial system that emerged to offer an alternative source of financing development particularly among some countries in the global South. The aim of this article is to explore the role of diplomacy in the emergence of IF as an alternative financing source particularly for the global South. This article argues that IF was born out of diplomatic process, like its counterpart the Bretton Woods system. It further argues that, to understand the emergence and the forces behind the emergence of Islamic financial system, there is need to look at the context of the notion of South-South Cooperation that was conceived in 1950s and gained momentum in 1960s. The notion of South-South Cooperation showed to the Muslim world the possibility of creating a new financial system that began with the formation of the Organization of Islamic Conference (OIC) in 1969 and consolidated with the Mecca Conference in 1976. This article concludes that although international financial systems are always the product of diplomacy, however, the nexus between the two has been overlooked by researchers. This article, therefore, recommends that future studies examine this relationship in an in-depth manner.